Effects of corticosteroid on the expressions of neuropeptide and cytokine mRNA and on tenocyte viability in lateral epicondylitis - Han Soo; An Hee; Song Ji; Shin Dong; Kwon Young; Shim Jong; Lee Soon (Journal of Inflammation, 2012)
Abstract Background The purpose of this study was to determine the reaction mechanism of corticosteroid by analyzing the expression patterns of neuropeptides (substance P (SP), calcitonin gene related peptide (CGRP)) and of cytokines (interleukin (IL)-1α, tumor growth factor (TGF)-β) after corticosteroid treatment in lateral epicondylitis. In addition, we also investigated whether corticosteroid influenced tenocyte viability. Methods The corticosteroid triamcinolone acetonide (TAA) was applied to cultured tenocytes of lateral epicondylitis, and the changes in the mRNA expressions of neuropeptides and cytokines and tenocyte viabilities were analyzed at seven time points. Quantitative real-time polymerase chain reaction and an MTT assay were used. Results The expression of SP mRNA was maximally inhibited by TAA at 24 hours but recovered at 72 hours, and the expressions of CGRP mRNA and IL-1α mRNA were inhibited at 24 and 3 hours, respectively. The expression of TGF-β mRNA was not significant. Tenocyte viability was significantly reduced by TAA at 24 hours. Conclusions We postulate that the reaction mechanism predominantly responsible for symptomatic relief after a corticosteroid injection involves the inhibitions of neuropeptides and cytokines, such as, CGRP and IL-1α. However the tenocyte viability was compromised by a corticosteroid.